2022
DOI: 10.1155/2022/4230236
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Investigation of the Potentialities of a Mesoscale Meteorological Model to Reproduce Experimental Statistics of Rain Attenuation on Earth-Space Links

Abstract: Current spatial resolutions achieved by mesoscale weather forecast models allow them to be used to generate the state of the lowest layers of the atmosphere over areas as small as a few square kilometers which corresponds to the typical size of the tropospheric area crossed by Earth-space links. Furthermore, they allow the evolution of the troposphere to be predicted with a time stamp of five minutes instead of every hour with large-scale weather forecast models which makes them attractive for radio propagatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…the number of rain drops per unit mass of dry air. The details on how to use these variables to get to Λ or (𝑁 𝑅 , Λ), for a single or double-moment distribution respectively, are laid out in [12], [14] and [27] respectively.…”
Section: Rain Attenuation Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…the number of rain drops per unit mass of dry air. The details on how to use these variables to get to Λ or (𝑁 𝑅 , Λ), for a single or double-moment distribution respectively, are laid out in [12], [14] and [27] respectively.…”
Section: Rain Attenuation Modelmentioning
confidence: 99%
“…It was generally observed that simulated rain attenuation time series correlate poorly with measurements (10-30%). However, acceptable agreements (within 1-5 dB) have been reported for the corresponding rain attenuation Complementary Cumulative Distribution Functions (CCDFs) [12], [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The WRF‐EMM combined approach presented here is based on the Weather Research and Forecasting (WRF) model developed by NCAR/National Centers for Environmental Prediction (NCEP) in the US and on an ElectroMagnetic Module (EMM) developed by ONERA. It was used to compute annual statistics of attenuation in several regions (Castanet et al., 2022) such as Toulouse (Outeiral et al., 2013) (Quibus et al., 2022), the south of Europe (Fayon et al., 2017) as well as in Belgium and Italy (Quibus, 2020). It has also been tested in Kourou (Le Mire et al., 2020) where both annual and monthly statistics of rain attenuation have been compared to the measurements available on site (L’Hour et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The EMM physical propagation model converts the relevant WRF outputs concerning the propagation of radio waves to compute tropospheric attenuation due to oxygen, water vapor, clouds, and rain. More details on the EMM module can be found in LeMire et al (2020) andCastanet et al (2022).The parametrization of the WRF model to obtain an accurate simulation of the atmosphere is a critical aspect of the research studies surrounding this open-source research model. Due to the high number of input parameters as well as many different choices of parametrization, it is a complex exercise as can be shown in the literatureMourre et al (2016),Moya-Álvarez et al (2018), andRama Rao et al (2012).…”
mentioning
confidence: 99%